Cognitive training: How can it be adapted for surgical education?. Issue 4 (August 2017) - Wallace, Lauren; Raison, Nicholas; Ghumman, Faisal; Moran, Aidan; Dasgupta, Prokar; Ahmed, Kamran
Abstract: Background: There is a need for new approaches to surgical training in order to cope with the increasing time pressures, ethical constraints, and legal limitations being placed on trainees. One of the most interesting of these new approaches is "cognitive training" or the use of psychological processes to enhance performance of skilled behaviour. Its ability to effectively improve motor skills in sport has raised the question as to whether it could also be used to improve surgical performance. The aim of this review is to provide an overview of the current evidence on the use of cognitive training within surgery, and evaluate the potential role it can play in surgical education. Methods: Scientific database searches were conducted to identify studies that investigated the use of cognitive training in surgery. The key studies were selected and grouped according to the type of cognitive training they examined. Results: Available research demonstrated that cognitive training interventions resulted in greater performance benefits when compared to control training. In particular, cognitive training was found to improve surgical motor skills, as well as a number of non-technical outcomes. Unfortunately, key limitations restricting the generalizability of these findings include small sample size and conceptual issues arising from differing definitions of the term 'cognitive training'. Conclusions: When used appropriately, cognitive training can be a highly effective supplementary training tool in the development of technical skills in surgery. Although further studies are needed to refine our understanding, cognitive training should certainly play an important role in future surgical education.